Maternal factors associated with prematurity in pregnant women from a public hospital in Trujillo, Peru - Toro-Huamanchumo, Carlos J. (2021)
Background: The risk of prematurity includes a wide variety of complications at birth, such as infectious diseases, intraventricular hemorrhage, neurosensory deficiencies, respiratory failure and involvement of other systems, as well as growth and developmental problems. Therefore, the achievement of the Millennium Development Goal of reducing child mortality depends largely on the reduction of mortality related to premature birth, making it one of the most important challenges for modern public health. Objetive: To identify maternal factors associated with prematurity. Material and Methods: A retrospective case-control study was conducted on 2000 live newborns in a public hospital in Trujillo, between 2015-2019. The groups were divided according to the criteria of gestational age. The paired maternal clinical variables were analyzed according to prematurity or term, and a bivariate and multivariate analysis was made by logistic regression adjusted for confusers. Results: It was demonstrated that the number of prenatal controls less than four during gestation, is associated to prematurity (OR 2.65; IC95%: 2.21-3.18). On the other hand, the absence of a urinary tract infection (OR 0.73; IC95%: 0.56-0.95), is associated with lower risk of prematurity. Conclusions: The number of prenatal controls is an important associated factor for preterm delivery, while the absence of a UTI may be associated with a lower rate of preterm delivery in at-risk pregnancies.